The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s42452-020-03456-w
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cementitious composites with graphene oxide and carbon nanotubes

Abstract: Both graphene oxide (GO) and carbon nanotubes (CNTs) are carbon-based nanomaterials. Due to their favorable dispersibility in water and excellent mechanical properties, they are potential additives for use as reinforcements in cementitious composites. In this laboratory study, GO and CNTs were simultaneously used as additives to improve the mechanical properties (e.g., compressive strength) and durability (e.g., frost resistance, water impermeability) of cementitious composites. To maintain and optimize the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The findings of Du and Pang [98] further support the current findings, from their studies with GNP-reinforced (2.5 wt.%) cement mortar exhibited significant enhancements in moisture barrier properties. A recent study indicated that a combination of graphene oxide (GO) and CNTs can significantly reduce the water permeability of cementitious composites due to simultaneous bridging effect of CNTs and the nucleation effect of GO [99].…”
Section: Moisture Absorption Ratementioning
confidence: 99%
“…The findings of Du and Pang [98] further support the current findings, from their studies with GNP-reinforced (2.5 wt.%) cement mortar exhibited significant enhancements in moisture barrier properties. A recent study indicated that a combination of graphene oxide (GO) and CNTs can significantly reduce the water permeability of cementitious composites due to simultaneous bridging effect of CNTs and the nucleation effect of GO [99].…”
Section: Moisture Absorption Ratementioning
confidence: 99%